2018
DOI: 10.1101/261974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA Methylation Explains a Subset of Placental Gene Expression Differences Based on Ancestry and Altitude

Abstract: Abstract:Objectives: The most pronounced effect of high altitude (>2700m) on reproductive outcomes is reduced birth weight. Indigenous Bolivians (Andean Native Americans) residing for generations at high altitudes have higher birth weights relative to more recent migrants of primarily European ancestry. Previous research demonstrated that the placenta is a key contributor to the preservation of Andean birth weight at high altitude. Our current research investigated how gene expression and epigenetics contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…We first examined expression within an a priori gene set that included genes hypothesized to be relevant to altitude adaptation, placental physiology, and fetal growth outcomes in humans (43)(44)(45)(46)(47)(48)(49)(50)(51). Across its evolution, placentas have repeatedly co-opted genetic toolboxes and gene duplications from other tissues (52-54), and thus we might not expect there to be substantial overlap at the gene level between human and deer mouse gene sets that are associated with fetal growth outcomes and hypoxia responses.…”
Section: Genes Involved In Gestational Hypoxia and High Elevation Ada...mentioning
confidence: 99%
See 3 more Smart Citations
“…We first examined expression within an a priori gene set that included genes hypothesized to be relevant to altitude adaptation, placental physiology, and fetal growth outcomes in humans (43)(44)(45)(46)(47)(48)(49)(50)(51). Across its evolution, placentas have repeatedly co-opted genetic toolboxes and gene duplications from other tissues (52-54), and thus we might not expect there to be substantial overlap at the gene level between human and deer mouse gene sets that are associated with fetal growth outcomes and hypoxia responses.…”
Section: Genes Involved In Gestational Hypoxia and High Elevation Ada...mentioning
confidence: 99%
“…After filtering, mapping, and feature D R A F T assignment, our analysis included an average of 29.5M reads from our junctional zone/decidua samples (Range: 16.2 -39.3M), and an average of 31.3M reads from our labyrinth zone samples (Range: a priori dataset generation and analysis. We compiled a priori genes of interest from the literature, including genes hypothesized to be relevant to altitude adaptation and protection of fetal growth in 787 humans as well as genes with empirical evidence for differential 788 expression among lowland and highland human populations in the 789 placenta (39,45). Neither (39) nor (45) associate gene expression 790 with fetal growth outcomes, but instead focus on genes are differ-791 entially expressed between highlanders (Tibetans or Andeans) and lowlanders and hypoxia sensitivity.…”
Section: Rnaseq Data Generation and Analysis Tissue Was Homogenized Inmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that placental genes associated with cell fusion and proliferation, critical processes in placental development, were differentially expressed between individuals residing at high and low-altitude. Of 36 altitude-associated differentially expressed genes, 8 had significant correlation between gene expression and DNA methylation ( Gundling et al, 2018 ). One of these is dysferlin ( DYSF ).…”
Section: Introductionmentioning
confidence: 99%